Particularities of the course and treatment of non-ST elevation acute myocardial infarction: data from the REGION-IM registry - S. A. Boytsov; R. M. Shakhnovich; S. N. Tereshchenko; A. D. Erlikh; D. V. Pevzner; R. G. Gulyan; Yu. K. Rytova; D. V. Khegya; A. A. Khafizov; T. V. Kuzmicheva; A. N. Potapova; E. Yu. Gaskova; et al. (Российский кардиологический журнал)
Aim. To characterize patients with acute non-ST elevation myocardial infarction (NSTEMI) hospitalized in Russian hospitals, study their anamnestic, demographic and clinical characteristics, treatment features and hospital outcomes, as well as compare data from previous Russian and foreign registries of acute coronary syndrome.Material and methods. Russian Registry of Acute Myocardial Infarction (REGION-IM) is a multicenter prospective observational study. The case report form contains demographic and anamnestic data, as well as the following information about the present MI: timing of symptom onset, first contact with medical personnel and admission to the hospital; data from coronary angiography (CAG) and percutaneous coronary intervention (PCI), therapy, hospitalization outcomes.Results. In total, for the period from November 1, 2020 to June 30, 2023, the study included 3253 patients with STEMI from 73 hospitals (30 vascular surgery departments, 17 of which are equipped with angiographic system, and 43 regional vascular surgery centers) from 45 constituent entities of the Russian Federation. There were 55% of high-risk patients. CAG was performed in 83,73% of patients. In 81%, CAG was performed ≤24 hours from hospitalization. PCI was performed in 62% of patients with NSTEMI. Median onset-to-balloon time was 27 hours [10;77]. The median door-to-balloon time was 5 hours [1;20]. Inhospital mortality was 3%. In the group with CAG, compared with the group without CAG, inhospital mortality was lower (2% and 6%, respectively; p<0,05). In patients with a higher risk according to the GRACE, CRUSADE and ARC-HBR scales, CAG was performed less frequently.Conclusion. In patients with NSTEMI in Russian regions, there is a high frequency of CAG and PCI, including in the early stages. Inhospital mortality is low, especially in the invasive treatment group, and corresponds to data from international registries. In severely ill patients, revascularization is performed less frequently than in low-risk patients. There is room for increasing the prescription rate of modern effective anticoagulants and antiplatelet agents. In general, the quality of treatment for NSTEMI patients has improved in recent years.